Phase Velocity of Facial Blood Volume Oscillation at a Frequency of 0.1 Hz - Yoshida, Kenichiro; Nishidate, Izumi (Frontiers in Physiology, 2021)
Facial blood flow, which typically exhibits distinctive oscillation at a frequency of around 0.1 Hz, has been extensively studied. Although this oscillation may include important information about blood flow regulation, its origin remains unknown. The spatial phase distribution of the oscillation is thus desirable. Therefore, we visualized facial blood volume oscillation at a frequency of around 0.1 Hz using a digital camera imaging method with an improved approximation equation, which enabled precise analysis over a large area. We observed a slow spatial movement of the 0.1-Hz oscillation. The oscillation phase was not synchronized, but instead moved slowly. The phase velocity varies with person, measurement location, and time. An average phase velocity of 3.8 mm/s was obtained for several subjects. The results are consistent with previous studies; however, the conventional explanation that the blood flow at a certain point oscillates independently of adjacent areas should be corrected. If the primary origin of the movement is myogenic activity, the movement may ascend along a blood vessel toward the upstream. Otherwise, the oscillation and its propagation can be considered to be related to Mayer waves. By determining the mechanism, some questions regarding Mayer waves can be answered. The direction of the wave (upstream or downstream) provides important information.